2020
DOI: 10.7554/elife.54434
|View full text |Cite
|
Sign up to set email alerts
|

A non-linear system patterns Rab5 GTPase on the membrane

Abstract: Proteins can self-organize into spatial patterns via non-linear dynamic interactions on cellular membranes. Modelling and simulations have shown that small GTPases can generate patterns by coupling guanine nucleotide exchange factors (GEF) to effectors, generating a positive feedback of GTPase activation and membrane recruitment. Here, we reconstituted the patterning of the small GTPase Rab5 and its GEF/effector complex Rabex5/Rabaptin5 on supported lipid bilayers. We demonstrate a ‘handover’ of Rab5 from Rabe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 70 publications
3
39
0
Order By: Relevance
“…Consistent with the organelle-specific roles of Rab5a on early endosomes 14,56,57 and Rab1 in autophagy 30,58,59 , we found that Rab5a preferentially activates complex II over complex I, and Rab1a activates only complex I. The cryo-ET structure shows that the VPS15 WD40 and SGD domains, as well as the VPS34 C2 helical insertion (C2HH), make interactions with Rab5a (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with the organelle-specific roles of Rab5a on early endosomes 14,56,57 and Rab1 in autophagy 30,58,59 , we found that Rab5a preferentially activates complex II over complex I, and Rab1a activates only complex I. The cryo-ET structure shows that the VPS15 WD40 and SGD domains, as well as the VPS34 C2 helical insertion (C2HH), make interactions with Rab5a (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Cryo-ET enabled us to visualise the molecular organisation of Rab5a-GTP/ complex II assembly on membranes. The dynamic mode of complex II membrane attachment allows the activated VPS34 kinase to survey the membrane for available substrate and generate local enrichment of PI3P that enables patterning of tightly organised Rab-containing domains 14 that ultimately determine organellar identity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relaxing this condition by reversing the GTPase:GEF ratio produced multiple coexisting mesa patterns, despite the reaction kinetics remaining the same. These modeling results are in good agreement with the results of [63] that, for the first time in any known system, succeeded in the in vitro reconstitution of the GTPase pattern formation using only a minimal set of recombinant proteins and lipid-coated beads. This remarkable effort produced multiple mesa-type spots of Rab5-GTP that stably coexisted during the duration of experiment.…”
Section: Implications For Cellular Morphogenesissupporting
confidence: 87%
“…This is to actively recruit Rab7a to the maturing endosome, which is necessary for the convergence phase of Rab5 maturation. Formation of the initial Rab5 domains in the convergence phase might be spontaneous and GTP dependent, as found in cell-free studies ( Cezanne et al, 2020 ). Our FRAP experiments showed a gradual increase of the relative Rab5-immobile fraction, also indicating a GTP-dependent organization of Rab5-positive domains during convergence.…”
Section: Discussionmentioning
confidence: 69%